Cost-Utility Analysis of Lipegfilgrastim Compared to Pegfilgrastim for the Prophylaxis of Chemotherapy-Induced Neutropenia in Patients with Stage II-IV Breast Cancer - Akpo, Esse I. H.; Jansen, Irshaad R.; Maes, Edith; Simoens, Steven (Frontiers in Pharmacology, 2017)
Background: Lipegfilgrastim (Lonquex®) has demonstrated to be non-inferior to pegfilgrastim (Neulasta®) in reducing the duration of severe neutropenia (SN) in patients with stage II−IV breast cancer. Compared to pegfilgrastim, lipegfilgrastim also demonstrated statistically significant lower time to ANC recovery in cycles 1-3, lower incidence of SN in cycle 2 and lower depth of absolute neutrophil count (ANC) nadir in cycles 2 and 3. The aim of this study was to quantify the cost utility of lipegfilgrastim compared to pegfilgrastim in stage II−IV breast cancer patients, taking the perspective of the Belgian payer over a lifetime horizon. Methods: Two Markov models were developed to track on- and post-chemotherapy related complications, including SN, febrile neutropenia (FN), chemotherapy dose delay, chemotherapy relative dose intensity of less than 85%, infection, death rates, and quality-adjusted life years (QALYs). Data on costs (2015 value) and effects were obtained from literature, national references, and complemented by a survey of clinical experts using a modified Delphi method. Both deterministic and probabilistic sensitivity analyses were carried out. Outcomes measures included costs, QALYs and life-years (LY). Results: At current equivalent price of € 1 169, treatment with lipegfilgrastim was associated with overall costs of €9 845 versus €10 208 for pegfilgrastim and overall QALYs of 13.977 versus 13.925 for pegfilgrastim. Life expectancy was increased by 21 days (or 0.058 LY gained). The difference in costs stem from avoided infection, SN and FN cases in the lipegfilgrastim compared to the pegfilgrastim group. Similarly, the difference in QALYs was explained by the difference in the number of patients in the chemotherapy/ G-CSF Markov state followed by infection and FN between lipegfilgrastim and pegfilgrastim. The probability of lipegfilgrastim to be cost-effective compared to pegfilgrastim was 68%, 79% and 83% at the willingness-to-pay thresholds (WTP) of €10 000, €30 000 and €50 000 per QALY gained, respectively. At a WTP threshold of €30 000 per QALY gained, lipegfilgrastim was cost-effective up to €1 500 across all age bands and cancer stages, compared to the current price. Conclusions: Lipegfilgrastim is a cost-effective use of health care resources in patients with stage II-IV breast cancer.